Living donor liver retransplantation for primary non-function of liver graft following multivisceral transplantation in a pediatric patient - Hwang, Shin (Ann Hepatobiliary Pancreat Surg, 2020)
Multivisceral organ transplantation (MVOT) includes transplantation of three or more abdominal organs, generally including the small bowel, duodenum, stomach, liver, pancreas, and colon. We here presented the detailed procedures of repeat living donor liver transplantation for primary non-function of the first liver graft following MVOT in a pediatric patient. A 6-year-old girl with chronic intestinal pseudo-obstruction underwent MVOT with 5-year-old donor organs. However, the primary non-function of the liver graft developed, and an emergency living donor liver transplantation operation using a left lateral section graft was performed on the third day after MVOT. The donor was the patient’s father. Portal flow interruption induced ischemic congestion of the whole small bowel, thus we used a series of porto-caval shunt to reduce the risk of ischemic splanchnic congestion during recipient hepatectomy and graft implantation. Other surgical procedures were the same as the standardized procedures for left liver graft implantation. The graft-recipient weight ratio was 2.15. The patient was managed conservatively for 3 months and discharged in an improved condition at 4 months after MVOT. She finally passed away at 22 months after MVOT. We think that our experience will be helpful for surgeons to cope with portal vein clamping-associated splanchnic congestion during liver transplantation and other abdominal surgeries.